Strategi Model Pembelajaran Contextual Teaching And Learning Pada Mata Pelajaran Fiqih Dalam Meningkatkan Motivasi Belajar - Afillah Rizky Ilahi; Laily Masruroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to uncover the implementation of the Contextual Teaching and Learning (CTL) model in Fiqh subjects at MA Salafiyah Syafi’iyah Seblak Jombang. Additionally, it highlights how this strategy affects students' enthusiasm and learning motivation. The research examines three main aspects: the strategy for implementing the CTL model, the level of student learning motivation, and the relationship between the CTL strategy and the increase in motivation within the context of Fiqh learning.To investigate the phenomena under study, this research adopts a qualitative inquiry approach characterized by an in-depth case study. Essential data was collected through a series of meticulous observations, intensive face-to-face dialogues with school leaders, Fiqh teachers, and students, complemented by a review of relevant documents. The research was conducted at MA Salafiyah Syafi’iyah Seblak Jombang, which has actively implemented the CTL model in Fiqh learning. The researcher directly served as the primary instrument in collecting field data, interpreting findings, and analyzing the relationships between variables.The study reveals that the CTL model plays a crucial role in boosting students' learning enthusiasm. They demonstrated fervent spirit, actively asked questions, and took greater responsibility in mastering Fiqh material, given its inseparable relevance to the validity of their worship. The school also supported this method by providing facilities for practical worship, such as actual practice of wudu, shalat, and even funeral arrangements. The CTL learning model in Fiqh studies proved effective not only in honing cognitive intelligence but also in comprehensively instilling religious character and practical worship skills in students.